2000
DOI: 10.1002/(sici)1521-3919(20000101)9:1<47::aid-mats47>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic polymer brush in a mixture of incompatible liquids

Abstract: An analogue of the Alexander‐DeGennes box model is used for theoretical investigation of polymer brushes in a mixture of two solvents. The basic solvent A and the admixture B are assumed to be highly incompatible (Flory‐Huggins parameter χAB = 3.5). Thermodynamics of a polymer in the solvents A and B are described by parameters χB < χA ≤ 1/2. The equilibrium behavior of a brush is investigated in dependence on solvent composition, grafting density, polymer‐solvents and solvent‐solvent interactions. The possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The transition between collapsed and swollen states was analogous to that in a single-component solvent with changes in temperature or solvent quality. Later, Birshtein et al 35 considered solvents that had low mutual solubility. They found that the brush exhibited a first-order compositional transition characterized by spontaneous increase in height and adsorption of a good solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition between collapsed and swollen states was analogous to that in a single-component solvent with changes in temperature or solvent quality. Later, Birshtein et al 35 considered solvents that had low mutual solubility. They found that the brush exhibited a first-order compositional transition characterized by spontaneous increase in height and adsorption of a good solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also examined a conformational transition induced by an external deformation of the brush. 35,37 Lyatskaya and Balasch 34 considered by SCFT water sorption from oil−water mixture by dense hydrophilic brushes including a weakly acidic polymer that was allowed to dissociate. The water concentration in the mixture was shown to control the effective brush height, and the local density of polymer segments has a maximum at the interface that formed between the hydrophilic layer that consisted of water and hydrophilic polymer and the hydrophobic oil bulk.…”
Section: Introductionmentioning
confidence: 99%